MANAJEMEN REDAKSIONAL TRIBUNPEKANBARU.COM DALAM MENENTUKAN BERITA YANG LAYAK - Fitria, Cendikia Dwi; Nasution, Belli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
News has become a very important requirement for today's society, almost everyone wanted and needed information, a present .In a news portal which would provide a dish worthy news to its readers, not least for the sake TribunPekanbaru.com portal providing information to the public. The quality of the news would be the responsibility of the editor, which is the department that is directly in contact with the news. For that reason, this study aims to determine the editorial management of the news portal TribunPekanbaru.com and how election news..worth..posting. This research applies qualitative method with descriptive approach qualitative in TribunPekanbaru.com news portal, Jalan Sudirman no. 383. Subjects of study include chief editor, journalist coordinator, online coordinator, and one journalists, as well as some of those readers who are determined through purposive method. Data collection techniques used were observation, interview,and.documentation. The results showed first management function on the news portal editor TribunPekanbaru.com in determining a news worthy. TribunPekanbaru.com implement a planning done in a meeting that news content planning meetings, meetings budgeting, and evaluation. As for the organization. TribunPekanbaru.com have determined the distribution of any journalist for news. Then the execution begins from covering news material, gathering, writing, editing news on the website to which of the use of new media. Forms of surveillance that was done TribunPekanbaru.com one of which is the evaluation of the work on monitoring the news items that will be in the post is one application gatekeeper theory, besides TribunPekanbaru.com also open the service to provide criticism and suggestions from the readers of the portal via e-mail. Second, the election news worthy to be posted on the portal is news that meet the elements of decent news is, the news must be accurate, the news must be full, fair and balanced, the news should be objective, the news should be concise and clear, and the news should be warm. The entire series is a form of managerial process done in determining decent news for the community. Keyword : redaksional, manajemen, news worthy